Toward an Understanding of the Experiences of Deaf Gay Men: An Interpretative Phenomenological Analysis to an Intersectional View. Issue 14 (6th December 2022) - Beese, Lilli Erin; Tasker, Fiona
ABSTRACT: Similarities between developing a deaf identity and a sexual minority identity have been postulated upon the parallel experience of oppressed minority positions. Sign language interviews with eight deaf gay British men explored their intersectional understanding of deaf-gay lived experiences, analyzed through Interpretative Phenomenological Analysis. During their adolescence deaf gay men sometimes experienced being in a position where they were trying hard to be something they were not: oral and heterosexual for hearing non-signing others (including heterosexual members of their family of origin). Participants spoke of increasingly being drawn toward a welcoming signing cultural world that supported them against deaf minority stress. Coming out as gay presented not only potential family of origin difficulties, but also threatened connection with the deaf community, leaving participants intensely fearful of gay visibility and stigma. Self-fulfillment and community building was sought through positions that ranged from oralist-heteronormativity through to the deaf-gay community. Along the way these journeys included experiences of pride and success alongside those of struggle. Our findings extend research on intersectionality by presenting a distinct set of obstacles, caveats, and nuances to identity conjunction.